Centralization of liver cancer surgery and impact on multidisciplinary teams working on stage IV colorectal cancer - Elroy Patrick Weledji (Frontiers Media S.A., 2017)
Surgical resection is the most effective treatment approach for colorectal liver metastases but only a minority of patients is suitable for upfront surgery. The treatment strategies of stage IV colorectal cancer have shifted towards a continuum of care in which medical and surgical treatment combinations are tailored to the clinical setting of the individual patient. The optimization of treatment through appropriate decision-making and multimodal therapy for stage IV colorectal cancer require a joint multidisciplinary meeting in a centralized liver cancer unit.